Effects of n-3 EPA and DHA supplementation on fat free mass and physical performance in elderly. A systematic review and meta-analysis of randomized clinical trial. (June 2021) - Rondanelli, Mariangela; Perna, Simone; Riva, Antonella; Petrangolini, Giovanna; Di Paolo, Enrica; Gasparri, Clara
Highlights: Omega-3 fatty acids supplementation seems to have positive effect on skeletal muscle. Daily n-3 EPA + DHA supplementation improves Time Up and Go (TUG) test. N-3 PUFA-s intake could be a promising strategy to prevent and treat sarcopenia. Abstract: The most studied n-3 polyunsaturated fatty acids (n-3 PUFAs) are eicosapentaenoic acid (EPA; 20:5n−3) and docosahexaenoic acid (DHA; 22:6n−3), and their intake seem to have a positive effect on skeletal muscle. This systematic review and meta-analysis aims to investigate the effect of n-3 EPA and DHA supplementation on fat free mass, and on different indexes of physical performance in the elderly. Eligible studies included RCT studies that investigated EPA and DHA intervention. Random-effects models have been used in order to estimate pooled effect sizes, the mean differences, and 95 % CIs. Findings from 14 studies (n = 2220 participants) lasting from 6 to 144 weeks have been summarized in this article. The meta-analyzed mean differences for random effects showed that daily n-3 EPA + DHA supplementation (from 0.7 g to 3.36 g) decreases the time of Time Up and Go (TUG) test of −0.28 s (CI 95 %−0.43, −0.13;). No statistically significant effects on physical performance indicators, such as 4-meter Walking Test, Chair Rise Test and Handgrip Strength, have been found. The fat free mass follows an improvement trend of +0.30 kg (CI 95 % -0.39, 0.99) but not statistically significant. N-3 EPA + DHA supplementation could be a promising strategy in order to enhance muscle quality and prevent or treat frailty.